Planck constant - Leonidovich, Sokolnikov Mikhail; Lerunovich, Akhmetov Alexey (IJRDO-Journal of Applied Science, 2017)
The connection to the Planck constant with Wien's displacement law andKepler's third law. The exact value of Planck's constant for the liquid or solid stateof aggregation of matter equals toh = 4*10-34 J*s.The formula that combines four physical constants - the speed of light - c,Wien's displacement constant - в, Planck constant - h and the Boltzmann constant- k3kв = hс